LOCUS OF CONTROL TERHADAP HASIL BELAJAR AKADEMIK SMA NEGERI 1 TERNATE - Siti Umairah; Fiki Febrian Dwi Prasetya; Liasari Armaijn (Pelantar Press, 2026)
This study aims to determine the locus of control on academic learning outcomes of State Senior High School 1 Ternate. The sample in this study amounted to 35 students in 35 students at State Senior High School 1 Ternate with an age range of 16-18 years. The subjects of this study were selected using the Spearman Rho test technique. The method used in this study is a quantitative research method with a measuring instrument in the form of a locus of control scale. The results of the analysis showed no significant correlation between locus of control and academic learning outcomes (r = 0.452, sig <0.05), that learning outcomes are relatively permanent behavioral changes in a person rather than locus of control